Chitosan-based near-infrared fluorescent micelles for controlled drug delivery and bioimaging in cancer therapy. (8th May 2023) - Cheng, Peiyun; Liang, Na; Zhao, Wei; Gong, Xianfeng; Wang, Weijia; Sun, Shaoping
Graphical abstract: Highlights: A chitosan-based near-infrared fluorescent polymer was designed and synthesized. The polymer was used as a micellar carrier for paclitaxel. The micelles exhibited NIR imaging, tumor targeting and pH-responsive properties. The micelles could reduce the adsorption of proteins on particles. The micelles would be promising candidate for bioimaging and cancer therapy. Abstract: In this study, an amphiphilic polymer mPEG-CS-Bio-Hz-Q with capabilities of near-infrared (NIR) fluorescence imaging, active tumor targeting, minimized protein adsorption and pH-responsive drug release was designed and synthesized. The polymer was served as a micellar carrier for paclitaxel (PTX) delivery. The mean size of PTX-loaded mPEG-CS-Bio-Hz-Q micelles was 123.5 nm. In vitro drug release study indicated the pH-triggered PTX release behavior of the micelles. Cellular uptake study demonstrated that the micelles could be effectively internalized by MCF-7 cells and exhibit bright fluorescence. In vivo investigation illustrated the high antitumor activity and excellent safety of the micelles. The mPEG-CS-Bio-Hz-Q micellar system would be promising candidate for bioimaging and cancer therapy.